2022
DOI: 10.1002/pad.1987
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the role of civic organizations in Kazakhstan, Kyrgyzstan, and Tajikistan: Confidence, membership, and democratic practice

Abstract: In many emerging and authoritarian countries, civil society organizations that focus on political or sensitive policy issues are being cracked down upon, while serviceoriented ones are given a relatively greater ability to operate. What might the consequence of this be for democratic practice given the important role civic organizations play in this process? We examine this question by considering whether the absence of confidence in a country's governing institutions is related to membership in service-rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…To explain variations in co‐optation and control of CSOs in authoritarian settings, research has explored variations between different policy sectors and found that repression of CSOs is particularly high where organisations work on politically contentious topics and advocacy rather than service provision (Hildebrandt, 2013; Yerkes, 2012). While those insights are interesting, they fail to account for the fact that service provision and policy advocacy often overlap (Fisher Melton, 2023; Herrold & AbouAssi, 2023; Moldavanova et al., 2023; Moldogaziev & Witko, 2023). Moreover, they are ill suited to explain why CSOs working on the same topics sometimes differ regarding their ability and willingness to drive an independent agenda from the state (Pellerin, 2019b).…”
Section: Analysing Civil Society—state Relations Under Non‐democratic...mentioning
confidence: 99%
“…To explain variations in co‐optation and control of CSOs in authoritarian settings, research has explored variations between different policy sectors and found that repression of CSOs is particularly high where organisations work on politically contentious topics and advocacy rather than service provision (Hildebrandt, 2013; Yerkes, 2012). While those insights are interesting, they fail to account for the fact that service provision and policy advocacy often overlap (Fisher Melton, 2023; Herrold & AbouAssi, 2023; Moldavanova et al., 2023; Moldogaziev & Witko, 2023). Moreover, they are ill suited to explain why CSOs working on the same topics sometimes differ regarding their ability and willingness to drive an independent agenda from the state (Pellerin, 2019b).…”
Section: Analysing Civil Society—state Relations Under Non‐democratic...mentioning
confidence: 99%